A Molecular Theory of the Onset of Turbulence - Muriel, Amador; Novopashin, Sergei; Esguerra, Jose Perico; Gutierrez, Edgardo (Science Diliman: A Journal of Pure and Applied Sciences; Vol 11 No 2 (1999), 2007)
We review experimental data which shows the dependence of the critical Reynolds number on molecular composition. We then use the cell model of a gas to explain the onset of turbulence by the excitation of the internal degrees of freedom of molecules. Two sources of internal energy states are identified: quantum confinement for monoatomic molecules and rotational states of diatoms.
Keywords: turbulence, Reynolds number, molecules